Abdominal Applications of 4D Flow MRI - Riedel, Christoph; Lenz, Alexander; Fischer, Lutz; Li, Jun; Piecha, Feilix; Kluwe, Johannes; Adam, Gerhard; Bannas, Peter (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2020)
Background Four-dimensional flow magnetic resonance imaging (4D flow MRI) provides volumetric and time-resolved visualization and quantification of blood flow. This review presents an overview of possible applications of 4D flow MRI for non-invasive assessment of abdominal hemodynamics.Method This review is based on the authors’ experience and the current literature. A PubMed database literature research was performed in December 2019 focusing on abdominal applications of 4D flow MRI. We illustrated the review with exemplary figures and movies of clinical cases from our institution.Results and Conclusion 4D flow MRI offers the possibility of comprehensive assessment of abdominal blood flows in different vascular territories and organ systems. Results of recent studies indicate that 4D flow MRI improves understanding of altered hemodynamics in patients with abdominal disease and may be useful for monitoring therapeutic response. Future studies with larger cohorts aiming to integrate 4D flow MRI in the clinical routine setting are needed.Key Points: Citation Format
Keywords: MRI; phase contrast MRI; 4D flow MRI; flow imaging; abdominal hemodynamics